2005
DOI: 10.1517/14728214.10.3.553
|View full text |Cite
|
Sign up to set email alerts
|

The development of erythropoietic agents in oncology

Abstract: The erythropoietic agents have achieved a remarkable degree of success as products for the treatment of anaemia associated with cancer chemotherapy. Three agents, epoetin-alpha, epoetin-beta and darbepoetin-alpha, share this global market and have demonstrated similar efficacy and share similar shortcomings, primarily a lower magnitude of cost/benefit than is the case for the dialysis patient. The continued success of these agents will depend on their ability to address the issue of resistance to therapy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The authors of meta‐analyses and systematic reviews [158,312‐318] suggest that patients receiving recombinant erythropoiesis‐stimulating agents (ESAs) to correct anemia measured at less than 10 g/dL may experience increased vigor and diminished fatigue. However, there is only limited evidence that ESAs improve fatigue when anemia is less severe, and the use of these agents must be considered in light of emerging safety issues, including an increased risk of thrombotic events, hypertension, and pure red cell aplasia, and concerns that ESAs may decrease locoregional disease control and survival outcomes in particular tumor types [318‐323]. Current national clinical practice guidelines [324] concluded that ESAs are not indicated for the treatment of CRF and restrict the use of ESAs for the treatment of anemia specifically related to myelosuppressive chemotherapy without curative intent.…”
Section: Interventions For Crfmentioning
confidence: 99%
“…The authors of meta‐analyses and systematic reviews [158,312‐318] suggest that patients receiving recombinant erythropoiesis‐stimulating agents (ESAs) to correct anemia measured at less than 10 g/dL may experience increased vigor and diminished fatigue. However, there is only limited evidence that ESAs improve fatigue when anemia is less severe, and the use of these agents must be considered in light of emerging safety issues, including an increased risk of thrombotic events, hypertension, and pure red cell aplasia, and concerns that ESAs may decrease locoregional disease control and survival outcomes in particular tumor types [318‐323]. Current national clinical practice guidelines [324] concluded that ESAs are not indicated for the treatment of CRF and restrict the use of ESAs for the treatment of anemia specifically related to myelosuppressive chemotherapy without curative intent.…”
Section: Interventions For Crfmentioning
confidence: 99%
“…30 Studies conducted on rHuEPO have shown that it improves patients' Hb levels and quality of life and decreases transfusion requirements. 33,34 It has been proposed that ESAs also improve the cognitive function of patients receiving chemotherapy. 35 A systemic review conducted by the American Cancer Society showed that optimal clinical benefit from erythropoietic treatment of chemotherapyinduced anemia may be achieved through early intervention.…”
Section: Treatmentmentioning
confidence: 99%
“…In a recent review by Glaspy, it was suggested that oncologists employ three times the amount of ESAs to gain 50-60 % of the benefit in transfusion reduction achieved by nephrologists treating dialysis-associated anemia. 61 This difference may be due to the almost universal use of iron supplementation for nephrology patients taking ESAs.…”
Section: Future Directionsmentioning
confidence: 99%